Xpert MTB/RIF Ultra assay for the diagnosis of pulmonary tuberculosis in children: a multicentre comparative accuracy study. Issue 4 (October 2018) - Sabi, Issa; Rachow, Andrea; Mapamba, Daniel; Clowes, Petra; Ntinginya, Nyanda E.; Sasamalo, Mohamed; Kamwela, Lujeko; Haraka, Frederick; Hoelscher, Michael; Paris, Daniel H.; Saathoff, Elmar; Reither, Klaus
Highlights: Xpert Ultra detects tuberculosis in children with a superior sensitivity compared to Xpert. The sensitivity of Xpert Ultra is considerably lower in children than in adults. The decreased specificity of Xpert Ultra warrants further investigations. Xpert Ultra might improve speed and reliability of tuberculosis diagnosis in children. Abstract: Objectives: We evaluated the diagnostic performance of the novel next-generation Xpert MTB/RIF Ultra (Xpert Ultra) in comparison to Xpert MTB/RIF (Xpert) assay for the detection of paediatric pulmonary tuberculosis in high burden settings. Methods: From May 2011 to September 2012, children with suspected pulmonary tuberculosis were enrolled at two Tanzanian sites and sputum samples were examined using sputum smear, Xpert and culture. Xpert Ultra was tested between January and June 2017 using sputum pellets, which had been stored at −80°C. The diagnostic accuracy of Ultra versus Xpert was determined using well-defined case definitions as reference standard. Results: In total, 215 children were included. The median age was 5.4 years, the HIV prevalence was 52% and 13% had culture-confirmed pulmonary tuberculosis. When only the first available sample of each patient was analysed, the sensitivity of Xpert Ultra was 64.3 % (95% CI: 44.1 to 81.4) while that of Xpert was 53.6% (95%CI: 33.9 to 72.5). The specificity of Xpert Ultra based on analysis of all available samples was 98.1% (95%CI: 93.4 to 99.7), that of Xpert was 100%. Conclusions: Xpert Ultra was found to have a higher sensitivity, but slightly reduced specificity compared to Xpert in detecting pulmonary tuberculosis in children.